Online Traffic Offence System (OnTOS) / Syahida Sani - Sani, Syahida (Faculty of Computer and Mathematical Sciences, 2007)
Online Traffic Offence System (OnTOS) is more about parking offence on the campus as well as issuing summon for offender. This web-based system contains some general information about the Mara University of Technology (UiTM) traffic offence. The PDA is use as a communication tool between user and the system and this system can retrieve and display all information about the vehicle. The objectives for this project are to identify the problem faced by the Security Centre, to design a model by using the new technology as an alternative way to the traditional PC-based Web browser for accessing the information and to develop an online system for use at the Security Centre. There are several crucial steps needed to be addressed to ensure that the data collection process and measurement systems are stable and reliable. Incorporating these steps into a data collection plan improved the possibility that the data can be used to support the ensuing analysis. The old system of collecting data has not proven effective or efficient for security guards. In the end of research project period, all the objectives in this research project have been achieved.